2014
DOI: 10.1590/0074-0276140033
|View full text |Cite
|
Sign up to set email alerts
|

Severity of chronic experimental Chagas' heart disease parallels tumour necrosis factor and nitric oxide levels in the serum: models of mild and severe disease

Abstract: Heart tissue inflammation, progressive fibrosis and electrocardiographic alterations occur in approximately 30% of patients infected by Trypanosoma cruzi, 10-30 years after infection. Further, plasma levels of tumour necrosis factor (TNF) and nitric oxide (NO) are associated with the degree of heart dysfunction in chronic chagasic cardiomyopathy (CCC). Thus, our aim was to establish experimental models that mimic a range of parasitological, pathological and cardiac alterations described in patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 53 publications
6
73
0
3
Order By: Relevance
“…At 150 dpi, 100% of the not-treated or saline-injected Colombian-infected C57BL/6 mice presented ECG alterations (as shown in Fig. 1E ), corroborating previous data [ 18 , 19 ]. At 160 dpi (40 days post-therapy initiation), 100% of rAdCtrl-injected mice presented ART and 70% presented AVB2 in a manner that 100% showed ECG abnormalities.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At 150 dpi, 100% of the not-treated or saline-injected Colombian-infected C57BL/6 mice presented ECG alterations (as shown in Fig. 1E ), corroborating previous data [ 18 , 19 ]. At 160 dpi (40 days post-therapy initiation), 100% of rAdCtrl-injected mice presented ART and 70% presented AVB2 in a manner that 100% showed ECG abnormalities.…”
Section: Resultssupporting
confidence: 91%
“…When C57BL/6 mice are infected with 100 blood trypomastigote (bt) forms of the Colombian strain, parasitemia peak occurs at 42–45 dpi, parasitemia control occurred from 60–70 dpi and chronic phase is established after 90 dpi, when none or rare blood trypomastigotes are detected [ 5 ]. Importantly, in this model of T. cruzi infection parasitemia and heart parasitism are directly associated and 70–85% of infected mice survived and developed a chronic disease with electrical abnormalities [ 5 , 18 ]. Therefore, vaccinated C57BL/6 mice were challenged with 100 bt forms of the Colombian strain and tested for heart tissue parasitism and electrical alterations in the acute and chronic infection ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the level of NO in the colonic tissue since T. cruzi induces upregulation of NO production in several tissues . We observed that the level of NO was reduced in infected mice treated with PBS, possibly due to the intense loss of nitrergic myenteric neurons and also because the inflammatory foci in the colonic wall did not stimulate release of interferon gamma (IFN‐γ).…”
Section: Discussionsupporting
confidence: 82%
“…19 Despite this pattern we found beneficial effects not only when T. cruzi mice were treated with ASA during the acute phase, but also during the chronic phase, ie, we We evaluated the level of NO in the colonic tissue since T. cruzi induces upregulation of NO production in several tissues. 3,36,37 We observed that the level of NO was reduced in infected mice treated with PBS, possibly due to the intense loss of nitrergic myenteric neurons and also because the inflammatory foci in the colonic wall did not stimulate release of interferon gamma (IFNγ). Infected mice treated with PBS had no detectable levels of interferon gamma (IFN-γ).…”
Section: (E) (F)mentioning
confidence: 99%
“…The degree of heart dysfunction is associated with a progressive inflammatory reaction, which is characterized by a myocarditis with multifocal mononuclear inflammatory infiltrates, a varied degree of myocardium fibrosis, a constant low-grade tissue parasitism, and a low or undetectable parasitemia [710]. …”
Section: Introductionmentioning
confidence: 99%